Development and Validation of the Gender/Race Acknowledgment and Disregard Scales (G/RADS) - Fine, Rachel D.; Schudson, Zach C.; Beischel, Will J.; Gelman, Susan A. (Sex Roles, 2025)
People can disregard or acknowledge social categories to mask or confront prejudice and discrimination in their everyday interactions. Yet little is known about the role of context in the expression of these judgments. Furthermore, research on disregard and acknowledgment of social categories has focused almost wholly on race (i.e., racial color-blindness and multiculturalism), to the exclusion of other social categories, such as gender. Accordingly, we developed the Gender/Race Acknowledgment and Disregard Scales (G/RADS) to assess individual differences in the degree to which people believe they disregard and/or acknowledge gender and race in their everyday interactions and their beliefs about structural disregard and acknowledgment. Across six studies we demonstrated that the G/RADS are internally reliable (Study 1a and 1b) and show acceptable test-retest reliability (Study 2a and 2b) and criterion-related validity (Studies 3a and 3b). We also demonstrated the importance of differentiating between systemic and interpersonal disregard and acknowledgment. In Studies 3a and 3b, we found that the intention to vote for candidates who acknowledged gender and race over candidates who disregarded gender and race was negatively correlated with systemic disregard and positively correlated with systemic acknowledgment. The G/RADS offers a new tool for investigating people’s complex attitudes, beliefs, and behaviors around race and gender.